Interaksi Sosial Anak dengan Hambatan Pendengaran pada Pembelajaran Kooperatif - Hestuaji, Yogi; Yulia, Yuyun; Cahyani, Berliana Henu (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
This study aims to describe the social interactions of children with hearing impairments in cooperative learning. The research strategy uses descriptive qualitative. The subject of this study was one student with hearing loss in grade IV. Data collection techniques in the form of observation and interviews. Based on the results of data analysis, it was found that the social interaction of children with hearing impairments in cooperative learning with their group mates was shown by having conversations in verbal and written language, carrying out collaborative activities in groups with division of tasks based on interests. Meanwhile, social interaction with PAI subject teachers is shown by having conversations using verbal and written language, and is very dependent on the mood to receive every instruction and direction.